Click beetles (Coleoptera: Elateridae) of Khuzestan province (Iran): with three new species, Craspedostethus izehensis sp.n., Dicronychus khuzestanicus sp. n. and Gurjevelater catei sp. n. - Nasserzadeh, Hiva; Platia, Giuseppe; Serri, Sayeh (Zootaxa, 2023)
More than 730 specimens of Elateridae were collected in Khuzestan province. Thirty three species belonging to 18 genera and five subfamilies are listed. Three new species, Craspedostethus izehensis sp. n., Dicronychus khuzestanicus sp. n., Gurjevelater catei sp. n. are described, along with the female of Aeoloides iranicus Platia & Gudenzi, 2002. Dicronychus houschkai Platia, 2011 is recorded as a new species to Iran. A distributional map and climate data for each species, along with photographs of habitus and genitalia of eight species are presented.